THE MAPPING OF TEA HARVESTING AREA USING PLANETSCOPE IMAGERY - Wikan Jaya Prihantarto; Muhammad Ismail; Eva Purnamasari; Kurnia Anggraini; Erisa Ayu Waspadi Putri; Hendry Frananda; Indah Setiawati (Remote Sensing Technology Study Program, 2025)
The identification of tea harvesting areas is an important part of tea culture. The use of satellite imagery for this application offers effectiveness. PlanetScope imagery has the advantage of high spatial, spectral, and temporal resolution and is widely used in agricultural and plantation studies. The objective of this study was to map tea pruning areas in the Danau Kembar Tea Plantation, Solok Regency, West Sumatra, using PlanetScope imagery. The images underwent radiometric, geometric correction and were then analyzed spectrally using the Normalized Difference Vegetation Index (NDVI) to obtain tea vegetation density classes. The image map resulting from this classification was used to identify the spatial distribution of harvesting and non-harvesting areas. The mapping results were validated by field surveys, and accuracy calculations were performed using the confusion matrix method. The findings showed that 250.50 hectares or 90.37% of the study area, are harvesting areas, with mapping accuracy reaching 84.0%. This study can provide an important reference for monitoring plantation land management, production estimation, and tea harvesting.